Determinants of Consumer Preference for New Energy Vehicle Charging Infrastructure-taking Zibo as an Example - Cao, Qingbo (Journal of Global Economy, Business and Finance, 2025)
The rapid adoption of new energy vehicles (NEVs) has intensified demand for efficient charging infrastructure. This study investigates consumer preferences for NEV charging stations in Zibo City leveraging survey data encompassing demographic, socioeconomic, and behavioral metrics. Key findings reveal distinct patterns in charging habits, location preferences, and satisfaction drivers across gender, age, occupation, income, and vehicle type. Public charging stations dominate among younger males, while home/company piles are favored by females and older cohorts. Cost sensitivity, safety concerns, and app functionality emerge as critical decision factors. Policy recommendations include tailored incentive programs, expanded private/commercial pile deployment, and standardized maintenance protocols to align with evolving user needs.